Case control study of association between the ANK3 rs10761482 polymorphism and schizophrenia in persons of Uyghur nationality living in Xinjiang China - ZHONG, Xianjiang (Shanghai Arch Psychiatry, 2014)
BACKGROUND: The rs10761482 polymorphism of the ANK3 gene has been associated with the occurrence of schizophrenia. AIM: Assess the relationship between the ANK3 gene and schizophrenia in individuals of Uyghurian descent. METHODS: A total of 630 patients with schizophrenia and 535 healthy controls of Uyghur descent were genotyped for the ANK3 gene rs10761482 locus using Taqman probe technology. SHEsis and SPSS17.0 software were used for data analysis. RESULTS: There were no significant differences in the genotype or allele frequencies between the case group and control group. Within the case group there was no relationship between gender or age of onset of schizophrenia and the genotype or allele frequencies. Separate analyses among men and among women also failed to identify significant differences in the allele and genotype frequencies between cases and controls or between patients with adolescent-onset schizophrenia and those with adult-onset schizophrenia CONCLUSION: Our findings do not support previous reports about the relationship of the ANK3 gene and schizophrenia. In the Uyghur nationality group recruited for this study there was no significant association between the ANK3 gene rs10761482 polymorphism and schizophrenia. If these results are replicated in further studies, then the focus should change to understanding why this widely acknowledged association does not exist in this particular ethnic group.